Organism-wide studies into pathogenicity and morphogenesis in Talaromyces marneffei. (April 2016) - Weerasinghe, Harshini; Payne, Michael; Beard, Sally; Andrianopoulos, Alex
Organism-wide approaches examining the genetic mechanisms controlling growth and proliferation have proven to be a powerful tool in the study of pathogenic fungi. For many fungal pathogens techniques to study transcription and protein expression are particularly useful, and offer insights into infection processes by these species. Here we discuss the use of approaches such as differential display, suppression subtractive hybridization, microarray, RNA-seq, proteomics, genetic manipulation and infection models for the AIDS-defining pathogen Talaromyces marneffei . Together these methods have broadened our understanding of the biological processes, and genes that underlie them, which are involved in switching between the saprophytic and pathogenic states of T. marneffei, the maintenance of these two specialized cell types and its ability to cause disease.